Impact of first wave of COVID-19 on outcomes of hospitalization for upper gastrointestinal bleeding in Hong Kong: a population-based study - Lui, Thomas K.L.; Tsui, Vivien W.M.; Leung, Wai K. (Endoscopy International Open, 2021)
Background and study aims The COVID-19 pandemic has caused a major disruption in the healthcare system. This study determined the impact of the first wave of COVID-19 on the number and outcome of patients hospitalized for upper gastrointestinal bleeding (UGIB) in Hong Kong. Patients and methods Records of all patients hospitalized for UGIB in Hong Kong public hospitals between October 2018 and June 2020 were retrieved. The number and characteristics of patients hospitalized for UGIB after COVID-19 was compared by autoregressive integrated moving average (ARIMA) model prediction and historical cohort. Results Since the first local case of COVID-19, there was an initial drop in UGIB hospitalizations (observed 29.8 vs predicted 35.5 per week; P = 0.05) followed by a rebound (39.8 vs 26.7 per week; P < 0.01) with a turning point at week 14 (Petitt’s test, P < 0.001). There was a negative association between the number of COVID-19 cases and the number of patients hospitalized for UGIB (Pearson correlation –0.53, P < 0.001). Patients admitted after the outbreak of COVID-19 had lower hemoglobin (7.5 vs baseline 8.3 g/dL; P < 0.01) and a greater need for blood transfusion (64.5 % vs baseline 50.4 %; P < 0.01), but similar rates of all-cause mortality (6.9 % vs 7.1 %; P = 0.82) and rebleeding (6.7 % vs 5.1 %; P = 0.11). There was also a higher proportion of patients with variceal bleeding (10.5 % vs baseline 5.3 %; P < 0 .01). Conclusions There was a dynamic change in the number of patients hospitalized for UGIB in Hong Kong during the first wave of the COVID-19 outbreak, with more obvious impact during the initial phase only.